Model Performance Supported SMEs Strategy-Based Applications Through E-Money Gofood Business Customer Satisfaction and Grabfood - Novita Ekasari; Nurhasanah Nurhasanah; Fitri Chairunnisa; Ade Perdana Siregar (Universitas Batanghari Jambi, 2019)
Advances in technology and modern lifestyle makes many emerging companies based financial technology (fintech), which offers various facilities through the application of e-based money where consumers are increasingly spoiled for culinary choice is especially promising business. This study aimed to determine the effect of the use of marketing strategies culinary SMEs belonging to the culinary application providers gofood and grabfood on its business performance through customer satisfaction service user business applications. Gofood and grabfood is a leading provider of Indonesia's biggest culinary applications so that users of these applications are very many in number. This study uses a sampling method in which samples used were 110 respondents business owners (business customers), which are small and medium businesses that have joined and cooperated with gofood and grabfood applications. This study has found that there is a direct or indirect effect of a positive and significant marketing strategy in which direct influence on the performance of SMEs has a percentage of 15.76%, while the influence of marketing strategies on the performance of SMEs through business customer satisfaction by 11.46%, while the influence overall 84.9%. From the research, it is recommended businesses (SMEs) can be more creative in creating a product presentation, updating prices, and provide promotional package that is more diverse and this strategy was evaluated in a certain period of time, other than that businesses can utilize the features of merchant review to assess the results business in the eyes of end consumers and improve the brand image of their business.